Unpacking the benefits of black soldier fly frass fertilizer towards nematode suppression and potato production - Emmanuel O. Anedo; Emmanuel O. Anedo; Emmanuel O. Anedo; Dennis Beesigamukama; Benson Mochoge; Nicholas K. Korir; Solveig Haukeland; Solveig Haukeland; Xavier Cheseto; Moses Nyongesa; Patrick Pwaipwai; Sevgan Subramanian; et al. (Frontiers in Plant Science)
Potato production is hindered by soil degradation and nematode infestation. Mineral fertilizers and synthetic nematicides are costly and cause negative impacts on humans and the environment, while organic fertilizers are less effective for soil health and nematode management. This study demonstrates the contribution of black soldier fly frass fertilizer (BSFFF) in nematode suppression and potato productivity when compared to commercial mineral fertilizer, organic fertilizer (SAFI), and nematicide. The on-farm experiments consisted of eight treatments: BSFFF, SAFI, BSFFF+5%chitin, NPK+nematicide, 50%BSFFF+50%NPK, 50%SAFI+50%NPK, 50%BSFFF+5% chitin+50%NPK, and control (unfertilized soil). Results revealed that all fertilizer treatments significantly increased potato growth, number of tubers (34 – 61%), and tuber yield (20 – 72%) relative to the control. Application of BSFFF+5% chitin produced 9 – 28% higher tubers per plant compared to other treatments. Over 26% higher tuber yield was achieved using BSFFF+5% chitin compared to NPK+nematicide treatment. Soil amendment with BSFFF+5% chitin caused 5–35% higher reduction in the number of cysts per 200 g soil-1 compared to NPK+nematicide and SAFI treatments. The same treatment reduced the PCN reproduction rate by 20% and 75% compared to NPK + nematicide and SAFI, respectively. Both BSFFF and NPK+nematicide treatments achieved comparable suppression of the number of eggs and infective juveniles (J2) per cyst-1 and eggs g-1 of soil. However, BSFFF+5% chitin reduced the number of eggs and J2 per cyst-1 and eggs g-1 of soil by 55–92% compared to SAFI. Our findings demonstrate that chitin-fortified BSFFF can significantly contribute to potato cyst nematode suppression and boost potato yields in smallholder farming systems, thus, making it a promising and sustainable alternative to commercial fertilizers and nematicides. Adopting this regenerative and multipurpose fertilizer will reduce reliance on synthetic fertilizers and nematicides, which are costly and harmful to the environment and human health.